Shrub diversity and girth sizes at old gy® nati&wa! pant, southwestern /germ: effect of annual burning on piliostigma tk^mngii (schum.) milne-redhead (2007)
Floristic survey of annually burned three wed: ::d vegetation was conducted on woody components Gj Old Oyo Nations. Park, Nigeria in 2005 to evaluate response of girths and species diversity to fire. A 50 m plot was used to systematica... assess the vegetation using twenty 3rd quadrats laid on four 50 m long transect in each plot. Girins a: os east heights »*s-?s estimated with tape at heights of 1.3 m on boles for girths > 10 cm. Coefficients of variation and various diversity indices were used to explain variation in girth sizes ana species diversity. The wetland of Ajaku had 1 8 species with gk ins >10 Cm while Ibuya and Ipade-Aya had 9 and 11 respectively. Largest girths were enumerated at Ajaku (up to 154.0 cm) and leas: girths at Ipade-Aya (up to 32.05 cm). Fire affected the recruitment of,species into large girth sizes. Piliostigma thinning,: (Schum.) Milne-Redhead, an important forage species was among species with intermediate to low girths at breast heigh: The response of the wetlands vegetation was indicated by the low dominance, despite high diversity of tolerable species Annual burning as a management tool is not goodfor the vegetation of the wetlands, unless timing is sv.cn inattne ecosystem is not fully dry in order to ameliorate the lethal fleets of fire on growing plants.